Competitive Marketing Vigilance and its Relationship to Social Persuasion Among a Sample of Sports Equipment Sales Representatives in Iraq - Suad Hasan Saeed; Qusay Rashid Sabti; Othman Adham Ali (International Journal of Educational Evaluation and Policy Analysis, 2024)
The rapid transformations that are taking place today and due to multiple factors, including modern technological development and intense competition between sports institutions at the local and global levels with the aim of controlling the sports market and achieving superiority, have put marketing representatives in difficult situations, and increasing pressure due to the demand of administrative officials in the field of sales to increase their sales and profits on the one hand, and on the other hand, the demand of sports consumers to satisfy their multiple and different needs and desires, in addition to the presence of competitors for the sports institution produced locally and globally. With high quality standards, the sports marketing job will face great and difficult challenges. The research aimed to identify the relationship between competitive marketing and social persuasion among a sample of sales representatives of sports teams in Iraq, whose number of representatives was (60) delegates randomly selected from the total community. The descriptive approach was used in the relational method of the relationship. Competitive marketing and social persuasion measures were distributed to the sample with the need to confirm the answer as an alternative, and once the answer was completed, the questionnaires were collected, audited and processed statistically using appropriate statistical means. The researcher found that: sales representatives are characterized by competitive marketing and have the ability to convince the social consumer of sports, the possession of representatives to a degree of competitive vigilance in marketing has a positive ethical relationship with their ability to convince the sports consumer socially. Therefore, the researcher recommends when choosing sales representatives the need to distinguish competitive marketing due to their role in convincing the consumer to buy.